Cytotoxic and Apoptotic Induction Potential of Extracts from Fermented Citrullus vulgaris Thunb. Seeds on Cervical and Liver Cancer Cells. (4th March 2021) - Ayo-Lawal, Rachael Aderonke; Osoniyi, Omolaja; Sibuyi, Nicole Remaliah Samantha; Meyer, Mervin; Ekpo, Okobi
Abstract: The anti-cancer activities of many fermented foods and beverages are now scientifically established. Ogiri-egusi is a condiment prepared from fermentation of Citrullus vulgaris (melon) seeds and consumed in many countries of West Africa. Its anti-oxidative and anti-hyperlipidaemic properties have been reported. This study investigated the anti-cancer activities of the aqueous and methanolic extracts from ogiri-egusi . Cytotoxicity was investigated using the MTT and colony-formation inhibition assays while flow-cytometer based Apopercentage assay was used to quantify apoptosis in extracts-treated cervical and liver cancer and normal human fibroblast cells. The inhibitory concentration responsible for killing 50% of cells after 24 h by the aqueous extract in KMST-6, HeLa, and Hep-G2 cells were estimated at 1.610, 1.020, and 1.507 mg/mL respectively. While these values reduced with increasing incubation time in cancer cells it increased in the non-cancer cell. Furthermore, the extract significantly induced apoptosis in HeLa (97 ± 0.18%) and Hep-G2 (73 ± 6.73%) cells. These findings were corroborated by cells morphologic presentations and inhibition of colony formation assay. These findings suggest that the aqueous extract from fermented Citrullus vulgaris seeds might be a nutraceutical with potential anti-cancer properties.